‘Schizophrenia’ in the Echo Chamber (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Drawing on the notion of 'the echo-chamber', this paper examines the existence of an insular bubble amongst existential psychotherapists when discussion turns to 'schizophrenia'. Improved dialogue between existential psychotherapy and contemporary psychiatry is encouraged with consideration as to how we might retain philosophical and ethical integrity for such conversations.
Keywords: Schizophrenia; psychosis; voices; psychiatry; medication; psychotherapy; freedom